KAPASITAS PEMERINTAH KOTA PEKANBARU DALAM PELAKSANAAN KEBIJAKAN SISTEM ZONASI SEKOLAH MENENGAH PERTAMA NEGERI DI KOTA PEKANBARU TAHUN 2019 - Jayanti, Chici; Anwar, Khairul (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The expectations of the community regarding the system and quality of education quality are getting higher. However, the many problems in the education system have caused the government to take a middle path by creating policies that are expected to solve these problems in education. The problems that exist in the education system, especially in Pekanbaru State Junior High School, currently are of various kinds, such as a lack of adequate facilities and infrastructure, discrimination in education and schools, unstable equality of education and so on. Therefore, the Ministry of Education and Culture initiated a policy called the Zoning System which aims at equitable education in Indonesia. This policy is implemented by the Pekanbaru City Government for equitable education in Pekanbaru City.The purpose of this study is to determine the Capacity of the Pekanbaru City Government in Implementing the Zoning System Policy for Public Junior High Schools in Pekanbaru City in 2019. This study uses a qualitative approach with a descriptive method. The research location is at the Pekanbaru City Education Office. In collecting data, the writer used interview and documentation techniques.The results of this study indicate that the zoning system has several objectives to be achieved by implementing this system for education in Indonesia. However, for SMPN Kota Pekanbaru there are still a number of objectives that have not been properly fulfilled. There are still several SMPNs in Pekanbaru that have slightly damaged or severely damaged classrooms. The poor condition of the classrooms is one of the reasons why some junior high schools have a shortage of new students. Other causes include: insufficient classrooms, poor classroom conditions, and also the scope of school zoning, where the distance between one school and another is close to a population of new students, which is more than the school.Keywords: Capacity, Local Government, Zoning System